Anti CD-6 monoclonal antibodies in the management of generalised pustular psoriasis - Mahendra M Kura; Anmol Sodhi; Avinash Sajgane; Ashish Karande (Wolters Kluwer Medknow Publications, 2022)
Generalised pustular psoriasis (GPP) is an uncommon, severe, life-threatening variant of psoriasis requiring careful therapeutic approach. Conventional treatment modalities have unsatisfactory outcomes, poor side effect profiles and toxicities that have led to an emerging use of biological therapies. Itolizumab, an anti-CD-6 humanised monoclonal IgG1 antibody, is approved for the management of chronic plaque psoriasis in India. We share our experience of using this drug in three cases of GPP that were failing conventional therapies. Its upstream effect on co-stimulatory pathway in disease pathogenesis is the postulated mechanism. Our experience warrants further large-scale exploration of the role of itolizumab in the management of GPP, which would benefit this severely affected population of patients. Although the definite pathogenesis of GPP is unknown fully, molecules blocking CD-6, which plays a role in the interaction between T cells and antigen-presenting cells (APCs), are expected as new promising treatment options for GPP.